Restructuring academic health services in the Western Cape : a critical evaluation with emphasis on a range of financial models developed to assist the process - De Beer, Zach (Department of Public Health and Family Medicine, 2017)
Various financial models were developed in the process of planning for the restructuring of academic health services in the Western Cape. In an attempt to inform and assist this process, these models are described, critically analysed and in certain cases further developed. Since most of these models are dynamic and have been developed within computer spreadsheet applications, the relevant files are included here on computer disk and form an integral part of this submission. The background to restructuring is first explored, the models are examined, and then the implications for policy, resource allocation and academic health services are discussed.